From Barbie to Renoir: Intellectual Property and Culture - Frankel, Susy (Victoria University of Wellington Law Review, 2010)
Barbie has become part of popular culture and this inaugural professorial lecture uses her iconic cultural status to discuss the relationship between culture and intellectual property. Intellectual property is frequently treated in New Zealand as primarily involving economic policy. However, it is also part of cultural policy. In her inaugural lecture, Professor Susy Frankel discusses how the articulation of the relationship between intellectual property and cultural values could lead to an improved intellectual property law for New Zealand, particularly in the fields of copyright and trade marks.